Integrasi Nilai Karakter Dalam Pembelajaran Ski Pada Era Merdeka Belajar (Studi Kasus di MTs. Irsyaduth Thullab Tahun 2024): Character Value Integration in Ski Learning In the Era of Independent Learning (Case Study at MTs. Irsyaduth Thullab in 2024) - Umami, Riza (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This study aims to describe the strategy and process of integrating character values in learning Islamic Cultural History (SKI) in the era of Merdeka Belajar at MTs. Irsyaduth Thullab in 2024. With a descriptive qualitative approach and case study method, data were collected through classroom observations, in-depth interviews with teachers, madrasah heads, and students, and analysis of learning documents. The results show that the integration of character values is carried out in a planned manner through the selection of exemplary-based historical materials, the application of active learning methods, and the preparation of contextual teaching modules. Values such as religiosity, responsibility, tolerance, and mutual cooperation are the main emphasis. The Merdeka Curriculum provides innovative space for strengthening character education through contextual learning. This research recommends training for teachers in designing value-based learning that is relevant and meaningful.